Access to online databases: predicate for faculty research output (2018)
The study examined the role of access to online databases as the basis for faculty research output in six universities (comprising two each of federal, state and private) in two Southwestern states in Nigeria. A descriptive research design guided the study. Multistage sampling procedures including purposive, stratification, randomization as well as proportionate sampling techniques were employed to select 339 faculty members who provided the data for the study. The data were collected using a structured questionnaire. Of the 339 copies of the questionnaires administered, 89 per cent were retrieved fully completed and found usable. The research questions that guided the study were analyzed using inferential statistics. Findings revealed that HINARI, ProQuest, JSTOR, and EBSCOhost were the most regularly accessible online databases. Incessant power supply and lack of downloadable full-text posed the greatest threats to online databases access. Similarly, the study found that the provision of full-text of most relevant research materials, steady power supply and acquisition of information literacy skills were the most effective ways of addressing online databases access constraints. Accordingly, the study recommended adequate funding of university libraries, provision of alternative means of power generation and increased user education for maximum exploitation of subscribed databases.